2000
DOI: 10.1348/135910700168739
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived risk, thought intrusiveness and emotional well‐being in women receiving counselling for breast cancer risk in a family history clinic

Abstract: Objectives. This study was designed to assess changes in perceived risk, cognitive intrusions and distress in women undergoing counselling for familial risk of developing breast cancer. Design. A longitudinal design in which 90 consecutive women attending a family history clinic were asked to indicate their concerns before counselling and then again 3 and 6 months post‐counselling. Method. Questionnaires included measures of thought content and intrusiveness, cancer specific distress (Cockburn, De Luise, Hurle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 29 publications
3
44
1
Order By: Relevance
“…These mean HADS scores are comparable to those found in other studies of women undergoing genetic counselling for breast/ovarian cancer risk (e.g. DudokdeWit et al, 1998;Kent et al, 2000;Lodder et al, 1999) and for women undergoing routine breast screening (Walker et al, 1994). Mean GHQ-28 scores were 21.2 (s.d.…”
Section: Clinicalsupporting
confidence: 84%
See 1 more Smart Citation
“…These mean HADS scores are comparable to those found in other studies of women undergoing genetic counselling for breast/ovarian cancer risk (e.g. DudokdeWit et al, 1998;Kent et al, 2000;Lodder et al, 1999) and for women undergoing routine breast screening (Walker et al, 1994). Mean GHQ-28 scores were 21.2 (s.d.…”
Section: Clinicalsupporting
confidence: 84%
“…Some of the few prospective studies that have examined how genetic counselling may influence levels of distress have found that general distress (Cull et al, 1999;Brain et al, 2000b) and cancer specific worry (Brain et al, 2000b;Kent et al, 2000) reduce following counselling, although others found no change (Watson et al, 1999). However, the group in the study by Watson et al (1999) were not split on the basis of their actual risk of developing cancer which may be likely to influence level of worry.…”
Section: Psychological Distressmentioning
confidence: 99%
“…In contrast, the studies that did not mention giving counselees this information observed no significant improvement of risk perception accuracy as a result of genetic counseling (Codori et al 2005;Kent et al 2000;Rothemund et al 2001), with the exception of one study (Kaiser et al 2004).…”
Section: Risk Perception Accuracymentioning
confidence: 75%
“…The current findings suggest that in women at lower risk, anxiety and cancer-related concerns were reduced after receiving personal risk information and there were high levels of satisfaction, regardless of whether this information was based on a detailed genetic analysis. Although some studies have shown no effect of providing risk information on psychological outcomes (Kent et al, 2000;Lloyd et al, 1996), this may reflect differences in the way that risk information is communicated. Improved psychological outcomes may be a function of services that not only provide specific risk information, but also address patients' emotional needs by offering appropriate reassurance (Watson et al, 1998).…”
Section: Discussionmentioning
confidence: 98%